2017
DOI: 10.1158/1078-0432.ccr-16-0698
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in PD-L1 Expression and Immune Infiltrates Early During Treatment Predict Response to PD-1 Blockade in Melanoma

Abstract: Disruption of PD-L1/cytotoxic T-cell PD-1 signaling by immune checkpoint inhibitors improves survival in cancer patients. This study sought to identify changes in tumoral PD-L1 expression and tumor-associated immune cell flux with anti-PD-1 therapies in patients with melanoma, particularly early during treatment, and correlate them with treatment response. Forty-six tumor biopsies from 23 patients with unresectable AJCC stage III/IV melanoma receiving pembrolizumab/nivolumab were analyzed. Biopsies were collec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
167
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(178 citation statements)
references
References 34 publications
8
167
1
2
Order By: Relevance
“…In contrast, it is well known that PD‐L1 expression in cancer is a dynamic phenomenon that is positively or negatively modulated by disease evolution and treatments . Indeed, tumors from responding patients treated with immunotherapy show early increases in immune infiltrating cells when rebiopsied . Although we are unaware of the mutational burden of the tumor of our patient, it is presumably high given the history of prolonged heavy smoking and alcohol consumption .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, it is well known that PD‐L1 expression in cancer is a dynamic phenomenon that is positively or negatively modulated by disease evolution and treatments . Indeed, tumors from responding patients treated with immunotherapy show early increases in immune infiltrating cells when rebiopsied . Although we are unaware of the mutational burden of the tumor of our patient, it is presumably high given the history of prolonged heavy smoking and alcohol consumption .…”
Section: Discussionmentioning
confidence: 77%
“…PD-L1 measured in tumor cells achieves 60% (I,J) infiltrating cells when rebiopsied. 13 Although we are unaware of the mutational burden of the tumor of our patient, it is presumably high given the history of prolonged heavy smoking and alcohol consumption. 1,4 Thus, nivolumab could be fairly viewed as the sole executive arm of the response seen in our patient.…”
Section: Discussionmentioning
confidence: 88%
“…First, several clones of anti-PD-L1 antibodies for IHC exist and their cut-off values are variable. 40,41 Second, PD-L1 is dynamic marker affected by concentration of IFN-c in the tumor microenvironment, 42 Third, the investigation target of PD-L1 expression is variable with the studies because PD-L1 is expressed in both tumor cells and immune cells. 43 Fourth, PD-L1 expression level is discordant between the primary tumors and metastatic sites, and is heterogeneous even in tumors.…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…These agents are now approved in certain adult tumors, such as melanoma. 8 With respect to CNS tumors, there is evidence in adult glioblastoma that PD-1's interaction with PD-L1 contributes to the profound immunosuppression seen in this tumor. 5 Our lab has shown that EPNs have significant infiltration of immune cells.…”
Section: Introductionmentioning
confidence: 99%